2002
DOI: 10.1063/1.1455699
|View full text |Cite
|
Sign up to set email alerts
|

Fractal cluster modeling of the fatigue behavior of lead zirconate titanate

Abstract: ; Ryu, J; et al., "Fractal cluster modeling of the fatigue behavior of lead zirconate titanate," Appl. Phys. Lett. 80, 1625Lett. 80, (2002; http://dx

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…One of the most popular high‐power materials, which is widely used in various commercial applications, is APC 841, manufactured by American Piezo‐Ceramics (APC) International (Mackeyville, PA). Extensive studies have been conducted on APC 841 in the last decade and have been reported in numerous publications 1–9 . Previously, we examined the use of this material for single and multilayer transformers 1,6–8 .…”
Section: Introductionmentioning
confidence: 99%
“…One of the most popular high‐power materials, which is widely used in various commercial applications, is APC 841, manufactured by American Piezo‐Ceramics (APC) International (Mackeyville, PA). Extensive studies have been conducted on APC 841 in the last decade and have been reported in numerous publications 1–9 . Previously, we examined the use of this material for single and multilayer transformers 1,6–8 .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, fractal domains have recently been used to understand long-time polarization dynamics in various modified PZTs. 10,11,25 The results of our investigation demonstrate that soft ferroelectrics contain such heterogeneities under field for EрE c , which control the dynamics of polarization switching. These heterogeneities are conceptually similar to the long-lived ones observed in relaxor ferroelectrics under weak field drive.…”
mentioning
confidence: 97%
“…However, 14% reduction of switchable polarization at 10 8 cycles was less than 17% found at 10 8 cycles in PZT thin films. It was demonstrated that a hard PZT was more stable under a continuous cyclical drive compared to pure PZT due to their inherent polarization pinning effect and good electrical strength [10].…”
Section: Cuo-cumentioning
confidence: 99%